Interface rich CuO/Al2CuO4 surface for selective ethylene production from electrochemical CO2 conversion. Issue 6 (4th April 2022) - Sultan, Siraj; Lee, Hojeong; Park, Sojung; Kim, Minho M.; Yoon, Aram; Choi, Hansaem; Kong, Tae-Hoon; Koe, Young-Jin; Oh, Hyung-Suk; Lee, Zonghoon; Kim, Hyungjun; Kim, Wooyul; et al.
Abstract : In this work, we designed a novel CuO/Al2 CuO4 catalyst by a phase and interphase engineering approach, which enables the electrochemical conversion of carbon dioxide to ethylene with ultrahigh activity and selectivity. Abstract : The electrochemical reduction of carbon dioxide (CO2 ) to multicarbon hydrocarbons or oxygenate compounds beyond carbon monoxide is of great importance, as it offers a promising way to obtain a renewable fuel of high energy density and close the carbon cycle. Copper has been considered the predominant and effective electrocatalyst for the CO2 reduction reaction (CO2 RR), especially when aiming for ethylene products. However, the selectivity or current density of most catalysts for ethylene production is not satisfactory at competitive prices. Here, we present a newly designed electrocatalyst comprising Al2 CuO4 nanosheets uniformly covered with CuO nanoparticles (CuAl-1 : CuO/Al2 CuO4 -23) by phase and interphase engineering, achieving an ultrahigh selectivity of 82.4% for ethylene in an H-cell system with good catalytic stability and material durability for 100 h. In a flow-cell electrolyzer, this catalyst achieves a remarkably high ethylene partial current density of 421 mA cm −2, substantially higher than the as-synthesized bare CuO (261 mA cm −2 ) counterpart. The results of time-resolved attenuated total reflection-surface enhanced infrared absorption spectroscopy (ATR-SEIRAS) suggest that compared to the CuO catalyst, CuAl-1 enabled high surface coverages of *CO intermediates and strengthened adsorption of *CO for C–C coupling toward *OCCO, which is an intermediate for the production of ethylene. X-ray absorption analysis confirms that Cu oxide species in CuAl-1 are well retained during CO2 reduction, whereas the bare CuO catalyst is completely reduced to the metallic Cu state. Density functional theory calculations propose that a synergistic effect between CuO and Al2 CuO4 in the CuAl-1 steers the CO2 RR pathway towards ethylene.